Climate change adaptation and international development : making development cooperation more effective - Fujikura, Ryō, 1955-; Kawanishi, Masato (Earthscan climate., 2011)
Climate change impacts upon the world's poorest most heavily. It is therefore essential that international development initiatives focus on improving the ability of developing countries to adapt to the effects of climate change. This book, a product of research by the JICA-RI (Research Institute of the Japan International Cooperation Agency), examines climate change adaptation from the perspective of development cooperation in order to provide useful lessons for those engaged in research, policy and practice in this vital area. In this book the editors have brought together a wide range of case.